Chemical Control of Pod and Seed Insect Caryedon Serratus (Coleoptera: Bruchidae) in Field - Sharma, Reema; Bhandari, R. S. (Indian Forester, 2012)
In the present study, an attempt was made to control pod and seed borer Caryedon serratus (Olivier) (Coleoptera: Bruchidae) infesting leguminous trees, in the field by systemic insecticides. For this two application methods Soil application and tree injection were tried. In both the methods random block designing was used taking G.B.H. (Girth at Breast Height) into consideration. The doses of insecticides were calculated according to girth class. Treatments were randomly allotted to the trees such that every girth class receives an application. In soil application method Phorate 10 G (organophosphate) was found better than carbofuron (carbamate). In tree injection method, dimethoate 30 EC and monocrotophos 36 EC, were applied and Dimethoate was found more effective.